Nahwa Tahdid al-Alaqah baina al-Ulum al-Syar'iyyah wa al-Ulum al-Ijtima'iyyah, Nazrah Tarikhiyyah Fikriyyah - Laith Su'ud Jassum al-Qaisi dan Iman Muhammad Abbas (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
Defining the relationship between the islamic sciences and the social Sciences has been an issue of controversy in the intellectual discourse in the Muslim world especially since the end of the ninteen century. this paper is an attempt to explore the historical background of this debatable issue which goes back to the late days of Ottoman calipathe and to identify the way muslim thinkers and Ulama rsponded to the incoming sciences and literature from the west, which ranges from those who were aware of the realities in dealing with the intellectual invasion and incoming cultural influences, to those who welcomed what they perceived as